Interaction between cadmium and zinc in barley (Hordeum vulgare L.) grown under field conditions - Akay, Aysen; Koleli, Nurcan (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The interaction between cadmium (0, 1, 2, 4 and 6 kg/da) and zinc (0, 1.5 and 3 kg/da) in barley (Hordium vulgare L. cv. Karatay-94) alone and in combination at tillering stage (3 - 4 leaf) grown under field conditions showed no phytotoxic symptoms. Cd application did not affect the grain yield of barley. Cd concentrations in flag leaf and grain increased marginally with increasing level of Cd but decreased with increasing Zn application. Cd and Zn application caused insignificant changes in N and K concentrations in barley. But P concentration in grain at especially Zn0 dose decreased with increasing level of Cd application. The effect of different doses of Cd and Zn on grains Cd content was found to be significant. Increased Cd doses generally decreased Zn content in grains. Â Key words: Interaction, Growth, Barley, Field conditions doi:10.3329/bjb.v36i1.1543 Bangladesh J. Bot. 36(1): 13-19, 2007 (June)